THE INFLUENCE OF MINERAL FERTILIZERS ON THE PRODUCTIVITY OF THE EAR, YIELD AND QUALITY INDICATORS OF SPRING WHEAT - Кудрявицька, Аліна; Карабач, Катерина; Гарячий, Ілля (SWorldJournal, 2024)
To obtain stable yields of spring wheat grain of the "Myronivska Yara" variety with correspondingly high grain quality indicators on moderately supplied nitrogen, phosphorus, and potassium meadow-chernozem carbonate light loam soil in a grain-beet crop ro